The Effectiveness of the National Library and Information System Authority of Trinidad and Tobago in its Role as a National Library - Renwick, Shamin; Williams, Ruth (My University, 2018)
The National Library and Information System Authority of Trinidad and Tobago (NALIS) aims to provide both the functions of a national library as well as a national library service. The objective of this study was to determine the effectiveness of NALIS in its role as a national library. Utilising a qualitative approach, the study used mixed methods: semi-structured interviews with NALIS’ senior management; review of the International Organization for Standardization performance indicators; and comparative analysis of the strategic plans of the National Library of Jamaica and NALIS. Findings revealed that, despite NALIS performing the functions of a national library, key aspects of its services remain unfulfilled. Participants could not agree on the description of NALIS as outlined in the NALIS Act but 60% concluded that, in their personal opinion, NALIS could best be described as a public library which provides a national library service. Point score analysis determined that the most important function was ‘Central Collection of the Nation’s Literature’. The strategic planning of NALIS was found to be in alignment with the age of the organisation, as it is currently in an early phase of operation when policy formulation is critical. Given the turbulent economic environment and the many constraints that NALIS faced, it proved to be effective in the performance of national library functions and continues to strive for excellence in service delivery. It was noted that effective quality management was not adequately performed. Thus, in order to improve the level of service delivery, better quality management measures must be implemented.